The training of physical education teachers in Portugal, the USA, and Brazil from the perspective of professionalization of teaching during the practicum - Dias, Fernanda Gosuen Gonçalves; Parreira, Renato Luis Tame; Pereira, Lucas de Freitas; Veneziani, Rodrigo Cássio Sola; Ambrósio, Maria Anita Lemos Vasconcelos; Almeida, Vinicíus Thomaz da Silva; Barros, Renata Alves de; Dias, Luis Gustavo Gosuen Gonçalves [UNESP]; Ambrósio, Sérgio Ricardo (Mary Lou Fulton Teacher College, 2022)
This research, with a qualitative approach of the multiple case study type, aimed to identify and analyze the influence of the movement for the professionalization of teaching (MPT) in three contexts of physical education teacher training practicum proposals. As a result, it was pointed out that in Portugal, the Bologna process represented the guiding principle of an integrated proposal for the European context for training and practicum; in the USA, the parameters prescribed in the manuals consolidated a proposal for teacher training and reorganized the practicum; and, in Brazil, the law of guidelines and bases for national education established principles for thinking about teaching as a profession and area of knowledge, promoting new interpretations for practicum. In conclusion, the MPT influenced training and the practicum in all contexts, but with different perspectives.
La formación de docentes de educación física en Portugal, Estados Unidos y Brasil sobre la perspectiva de profesionalización de la enseñanza en las prácticas supervisadas Resumen: La investigación, con un enfoque cualitativo del tipo estudio de caso múltiple, tuvo
A Formação de Professores de Educação Física em Portugal, EUA e Brasil sob a Perspectiva da Profissionalização do Ensino no Estágio Supervisionado1
Keywords: educational policies; physical education; practicum; teacher training